Habitat features and performance interact to determine the outcomes of terrestrial predator–prey pursuits. Issue 12 (12th October 2020) - Wheatley, Rebecca; Pavlic, Theodore P.; Levy, Ofir; Wilson, Robbie S.
Abstract: Animals are responsive to predation risk, often seeking safer habitats at the cost of foraging rewards. Although previous research has examined how habitat features affect detection by predators, little is known about how the interaction of habitat features, sensory cues and physical performance capabilities affect prey escape performance once detected. To investigate how specific habitat features affect predation risk, we developed an individual‐based model of terrestrial predator–prey pursuits in habitats with programmable features. We ran simulations varying the relative performance capabilities of predator and prey as well as the availability and abundance of refuges and obstacles in the habitat. Prey were more likely to avoid detection in complex habitats containing a higher abundance of obstacles; however, if detected, prey escape probability was dependent on both the abundance of refuges and obstacles and the predator's relative performance capabilities. Our model accurately predicted the relative escape success for impala escaping from cheetah in open savanna versus acacia thicket habitat, though escape success was consistently underestimated. Our model provides a mechanistic explanation for the differential effects of habitat on survival for different predator–prey pairs. Its flexible nature means that our model can be refined to simulate specific systems and could have applications towards management programmes for species threatened by habitat loss and predation. Abstract : While the ability to avoid predation is critical for survival, little is known about how sensory cues, habitat features and physical performance interact to affect escape performance. This individual‐based model explores how these interactions alter a prey's likelihood of detection by a predator and its chance of escaping if detected.